Short-Term Results of Multiwavelength Photobiomodulation in Retinitis Pigmentosa - Siqueira RC; Pinho TS; Brandão CC (Clinical Ophthalmology)
Rubens Camargo Siqueira,1,2 Tainara Souza Pinho,2 Cinara Cássia Brandão2 1Rubens Siqueira Research Center, São Jose do Rio Preto, Brazil; 2Faculty of Medicine of São Jose do Rio Preto—FAMERP, São Jose do Rio Preto, BrazilCorrespondence: Rubens Camargo Siqueira, Rubens Siqueira Research Center, Saldanha Marinho 2815 conj 42, Sao Jose do Rio Preto, SP, 15010-100, Brazil, Email siqueiraretina@gmail.comObjective: To assess the short-term effects of Multiwavelength Photobiomodulation (LumiThera Valeda Light Delivery System) on retinal functional behavior in patients with retinitis pigmentosa (RP).Materials and Methods: Twelve RP patients (24 eyes) underwent treatment involving nine photobiomodulation (PBM) sessions using the Valeda system, which emits three distinct wavelengths within the yellow (590 nm; 4 mW/cm2), red (660 nm; 65 mW/cm2), and near-infrared (NIR) (850 nm; 0.6 mW/cm2) spectrum. All evaluations were conducted four weeks post-therapy. The treated eye was compared with baseline (pre-therapy). Following nine PBM sessions, assessments included best-corrected visual acuity (BCVA), retinal sensitivity, and characteristics of the correction area via fundus automated perimetry using the Compass system. Additionally, a functional and structural assessment of the retina was performed using multifocal electroretinography (ERG), optical coherence tomography (OCT), fluorescence retinography (FR), and autofluorescence (AF). Statistical analysis employed the Student’s t-test for paired samples at a 95% confidence level (p-value ≤ 0.05).Results: LogMAR-based visual acuity assessment demonstrated an improvement in mean value from 0.62 to 0.53 logMAR, with a statistically significant p-value of 0.001. Visual field examination, based on mean deviation (MD), pattern standard deviation (PSD), and fundal perimeter deviation index (FPDI) parameters, showed improvement from − 19.87 dB to − 19.45 dB, 9.77 dB to 9.76 dB, and 37% to 39%, respectively, although with non-significant p-values of 0.366, 0.446, and 0.245, respectively. No adverse effects or abnormalities in optical coherence tomography (OCT) and electroretinogram (ERG) were observed during the follow-up period.Conclusion: In this short-term study, PBM appeared to have the potential to enhance BCVA and fundus automated perimeter in RP patients without causing significant adverse events. However, further assessment with a larger patient cohort and longer follow-up is warranted to ascertain the efficacy of this technique in these patients.Keywords: photobiomodulation, retinitis pigmentosa, LED, valeda, low-level laser therapy (LLLT)